2002
DOI: 10.1136/bjo.86.12.1369
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of oral antioxidant supplementation in ocular surface of diabetic patients

Abstract: Aim: To investigate the effect of vitamin C and E supplementation in the levels of nitrite, nitric oxide (NO) related metabolite, and ocular surface parameters in diabetic patients. Methods: 50 patients with non-insulin dependent diabetes mellitus were given vitamin C (1000 mg/day) and vitamin E (400 IU/day) supplementation for 10 days. Nitrite levels in tears were measured by photometric determination before and after vitamin supplementation. Tear function parameters (Schirmer test I, BUT, ocular ferning test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 48 publications
1
31
0
4
Order By: Relevance
“…In addition, a clinical study indicated that antioxidant therapy can improve some parameters on the ocular surface of diabetic patients [38]. However, it remains to be clarified whether symptoms associated with the lacrimal gland and/or tear film dysfunction observed in diabetic patients could be improved or reversed by anti-AGE strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a clinical study indicated that antioxidant therapy can improve some parameters on the ocular surface of diabetic patients [38]. However, it remains to be clarified whether symptoms associated with the lacrimal gland and/or tear film dysfunction observed in diabetic patients could be improved or reversed by anti-AGE strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Some ocular manifestations of DM are associated with lachrymal gland dysfunction and have been related to dry eye. Several clinical studies have demonstrated that people with DM are more vulnerable to dry eye than healthy subjects.…”
Section: Tear Filmmentioning
confidence: 99%
“…Dogru et al 17 showed, however, that the conjunctival metaplasia was due to a loss of neurotrophic effects as a result of corneal hypoesthesia, glucose level fluctuation, and metabolic control insufficiency. DM is often associated with increased oxidative stress and free radical production, 23,24 which may damage epithelial tissues such as the conjunctiva and the lachrymal glands. As the tear film is rich in several antioxidants such as ascorbic acid (vitamin C), found in high concentrations in the eye, Peponis et al 24 demonstrated that orally administered antioxidant supplements for a period of 10 days improved the tear film stability and secretion, and the antioxidant properties of vitamins C and E could protect the ocular surface from the attack of free radicals and preserve the integrity of the epithelium.…”
Section: Tear Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental study on diabetic rats suggested that nutritional vitamin E supplementation helps fatty acids metabolism and lower lipid peroxidation in rat tissues (50). Oral vitamin C and vitamin E has the ability to lower the oxidative stress in eye (51) and the vascular endothelia function get better in type1 and not type 2 diabetes (52). Vitamin C and Vitamin E, probably have an important role in reducing the oxidative www.intechopen.com Diabetes, Oxidative Stress, Antioxidants and Saliva: A Review 307 damage produced by nitric oxide and other free radicals.…”
Section: Diabetes and Antioxidantsmentioning
confidence: 99%